Bibliometric analysis of hypoxia inducible factor prolyl hydroxylase inhibitor in anemia - Zheng, Li; Liu, Ming; Zhang, Yatong; Zhang, Kaihua; Gu, Yanting; Liu, Deping (Frontiers in Pharmacology, 2022)
Objective: This study aimed to explore the global research status, hot topics, and future prospects in the field of the hypoxia inducible factor prolyl hydroxylase inhibitor(HIF-PHI) by bibliometric analysis. Methods: The literatures about HIF-PHI were downloaded from the Web of Science Core Collection and Pubmed database from inceptions to January.10st. 2022. The VOSviewer 1.6.18 was used to explore the bibliometric networks and research priorities of HIF-PHI. Results: A total of 409 papers about HIF-PHI were included, involving 1674 authors from 548 institutions in 43 countries. The number of HIF-PHI literatures showed an upward trend, with steady growth from 2015 to 2020 and rapid growth in 2021. Tadao Akizawa, Masaomi Nangaku and Alexander R Cobitz published the most literatures. The United States, Japan and China contributed the most publications. The three most contributed institutions are Astellas Pharma Inc, the Showa University and Glaxosmithkline. Therapeutic Apheresis and Dialysis, American Journal of Nephrology and Clinical Pharmacology in Drug Development are the most productive journals. The main hot topics of HIF-PHI field are anemia, chronic kidney disease, hif-phi, epoetin and roxadustat. Conclusion: The United States and Japan are dominant in the field of HIF-PHI research. The discovery and clinical application of HIF-PHI is a great boon for patients with renal anemia. However, due to the short clinical application time of HIF-PHI, and its long-term efficacy and safety still need time to prove. In addition, more cooperation should be carried out between European and American countries and Asian countries to better prove the clinical value of HIF-PHI.